Polymer cement waterproof coating capable of forming film at low temperature as well as preparation method and application of polymer cement waterproof coating

By using propylene glycol and lithium chloride in polymer cement waterproof coatings, the problem of emulsion structural damage caused by moisture condensation is solved, film formation and construction stability are achieved in the environment of minus ten degrees Celsius, and application needs are met under low temperature conditions. .

CN119161756APending Publication Date: 2024-12-20JIANGSU CANLON BUILDING MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411435489.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing polymer cement waterproof coatings are unable to react with cement at zero degrees and lower temperatures due to moisture condensation, which limits their application in winter and low temperature conditions.

Method used

Use propylene glycol as a protective medium to control the lower moisture content and appropriate amount of propylene glycol in liquid component A, keep the moisture in the liquid state, and add lithium chloride to powder component B to reduce the freezing point of water and promote cement. Hydration reaction ensures the stability and construction of materials under low temperature environments.

Benefits of technology

It realizes the film formation of polymer cement waterproof coatings under minus ten degrees Celsius, and meets the requirements of coating performance, ensuring the stability of construction and application under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086452000000081
    Figure BDA0005086452000000081
Patent Text Reader

Abstract

The invention relates to a low-temperature film-forming polymer cement waterproof coating as well as a preparation method and application thereof. The polymer cement waterproof coating comprises a component A and a component B, the component A comprises the following components in percentage by weight: 35%-60% of a film-forming polymer, 5%-20% of water, 30%-50% of propylene glycol and 0.6%-5.3% of sodium polyacrylate; the component B comprises the following components in percentage by weight: 25%-45% of cement, 45%-75% of quartz sand and 0.5%-3% of lithium chloride. The component A is obtained by performing vacuum extraction on a precursor of the component A. The polymer cement waterproof coating can form a film in an environment of-10 DEG C, the film coating performance can be guaranteed, and the polymer cement waterproof coating can be used under a low-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-temperature film-forming polymer cement waterproof coating and a preparation method and application thereof. Background Art

[0002] Polymer cement waterproof coating is a waterproof material widely used in the construction industry, and it plays an important role in various application scenarios. Polymer cement waterproof coating has excellent performance and protects the structure of the building from the damage of humid environment. The introduction of polymer materials makes it have strong weather resistance and durability, and can maintain stable waterproof function for a long time, reducing the cost and frequency of building maintenance. The cement component in the material can form a chemical bond with the concrete structure and fuse with the building structure, so that the polymer cement waterproof coating is firmly attached to the surface of the building material, giving full play to the design performance of the material. The high elasticity of polymer cement waterproof coating can make up for the leakage caused by cracks in the building structure and impact during use, so as to achieve functional guarantee under long-term work.

[0003] With the acceleration of urbanization and the continuous improvement of people's requirements for building quality, this polymer cement waterproof coating has gradually been used in more construction projects, providing reliable protection and support for living buildings and urban construction, and has a broad development prospect. However, polymer cement waterproof coating uses water as a dispersion medium. At zero degrees or lower temperatures, the condensation of water will destroy the polymer emulsion structure and fail to react with cement, making the material unable to be used in construction, limiting the application of such materials in winter and some low temperature conditions. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an improved polymer cement waterproof coating in view of the shortcomings and deficiencies of the prior art. The polymer cement waterproof coating can form a film in an environment of minus ten degrees, and the coating performance can be guaranteed, and can be used under low temperature conditions.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A polymer cement waterproof coating comprises component A and component B. Calculated by weight percentage of component A, component A comprises: 35%-60% of film-forming polymer, 5%-20% of water, 30%-50% of propylene glycol, and 0.6%-5.3% of sodium polyacrylate; calculated by weight percentage of component B, component B comprises: 25%-45% of cement, 45%-75% of quartz sand, and 0.5%-3% of lithium chloride.

[0007] The polymer cement waterproof coating in the prior art uses water as a dispersion medium. At zero degrees or lower temperatures, the condensation of water will destroy the structure of the polymer emulsion and make it impossible to react with cement, making the material unable to be used in construction, limiting the application of such materials in winter and under some low temperature conditions. If water is not used as a dispersion medium, or if the water content in the polymer emulsion is too little and the solid content is too high, the polymer emulsion cannot exist stably and is easily demulsified, and it can no longer react with cement to form a polymer cement waterproof coating.

[0008] The inventor of the present application has found through research that by using propylene glycol as a protective medium, applying propylene glycol to the polymer emulsion component, using polymer emulsion and propylene glycol simultaneously in liquid component A, and controlling the lower water content and the appropriate amount of propylene glycol in liquid component A, it is possible to achieve stable dispersion of polymer emulsions such as acrylates, and to minimize the amount of water, so that under low temperature conditions of zero degrees or lower, the water in component A can remain in a liquid state and will not condense. The liquid water and propylene glycol together achieve the fluidity of the liquid component at low temperatures, maintain the dispersion function of polymers and cement in a low temperature environment; and then achieve the hydration and condensation of water with cement in a liquid molecular state in a low temperature environment. That is, the present invention controls the specific dosage range of propylene glycol and water in component A, and at the same time, meets the demand for cement hydration water, ensures cement hydration and consolidation, reduces the amount of residual water, and prevents freezing from damaging the coating after construction.

[0009] In addition, the lithium chloride added to the powder component B can lower the freezing point of the water in the liquid component A, and replenish moisture by absorbing water molecules in the ambient air, thereby promoting the hydration reaction of cement and water after construction, and further helping to realize the application and construction of polymer cement waterproof coatings in low temperature environments.

[0010] In some embodiments, the number average molecular weight of the sodium polyacrylate is 100,000 to 400,000, preferably 300,000 to 400,000. The high molecular weight sodium polyacrylate is usually used as a thickener, and its main chain is a polyacrylic acid structure and the side chain is a sodium salt structure.

[0011] In some embodiments, the film-forming polymer is selected from a combination of one or more of acrylate polymers, styrene-acrylate polymers, and silicone-acrylate polymers.

[0012] Preferably, the film-forming polymer is an acrylate polymer.

[0013] Furthermore, the film-forming polymer and water exist in the form of a film-forming polymer emulsion.

[0014] In some embodiments, the component A further comprises an auxiliary agent, and the auxiliary agent is selected from a combination of one or more of a defoaming agent, a preservative, a color paste and a wetting agent.

[0015] Preferably, the auxiliary agent is a defoaming agent.

[0016] Furthermore, in terms of weight percentage, the component A includes 0.23%-0.9% of auxiliary agent.

[0017] In some embodiments, based on the weight percentage of component A, component A includes 35%-60% of film-forming polymer, 5%-20% of water, 30%-50% of propylene glycol, 0.6%-5.3% of sodium polyacrylate, and 0.23%-0.9% of defoaming agent.

[0018] In some embodiments, the component A is obtained by vacuum extraction of a precursor of component A; in terms of weight percentage, the precursor of component A includes: 30%-40% film-forming polymer, 25%-40% water, 30%-40% propylene glycol, and 0.5%-3.0% sodium polyacrylate.

[0019] In some embodiments, the film-forming polymer and water are present in the form of a film-forming polymer emulsion.

[0020] In some embodiments, the precursor of component A further comprises an auxiliary agent, and the auxiliary agent is selected from a combination of one or more of a defoaming agent, a preservative, a color paste and a wetting agent.

[0021] Preferably, the auxiliary agent is a defoaming agent.

[0022] Furthermore, the precursor of component A includes 0.2%-0.5% of an auxiliary agent by weight.

[0023] More preferably, the precursor of component A comprises 0.2%-0.5% of defoaming agent by weight.

[0024] In some embodiments, the component A is prepared by a preparation method comprising the following steps: dispersing the sodium polyacrylate into the propylene glycol, adding other raw materials of the precursor of component A, heating, and vacuum extraction to obtain the component A. The present invention selects sodium polyacrylate as a dispersant, which has a synergistic effect with propylene glycol. Sodium polyacrylate can help disperse propylene glycol and polymer emulsion on the one hand, and can also inhibit the volatilization of propylene glycol in the precursor of component A during the vacuum extraction process on the other hand, thereby reducing the waste of propylene glycol raw materials.

[0025] In some embodiments, the particle size of the quartz sand is 100-200 mesh.

[0026] In some embodiments, the component B further comprises an auxiliary agent, and the auxiliary agent is selected from a combination of one or more of a water reducing agent, a defoaming agent, a preservative, a color paste and a wetting agent. The above auxiliary agents can be conventional in the art.

[0027] Preferably, based on the weight percentage of component B, component B includes 0.2%-1.0% of the auxiliary agent.

[0028] In some embodiments, the cement is selected from white cement, gray cement, or a combination of both.

[0029] Preferably, the cement is white cement; further preferably, the cement is 42.5 white cement.

[0030] In some embodiments, the mass ratio of component A to component B is 1:1.5-2.0.

[0031] The present invention further provides a method for preparing the above polymer cement waterproof coating, the preparation method comprising the following steps:

[0032] 1) dispersing sodium polyacrylate in propylene glycol, adding other raw materials of the precursor of component A, stirring and mixing, and obtaining the precursor of component A;

[0033] 2) heating the precursor of the component A and vacuum extracting to obtain the component A;

[0034] 3) Mixing the component A and the component B to obtain the polymer cement waterproof coating.

[0035] In some embodiments, the stirring and mixing in step 1) is performed in a vacuum stirring device.

[0036] In some embodiments, the heating temperature in step 2) is 80-100°C.

[0037] In some embodiments, the vacuum extraction in step 2) is performed at a negative pressure of -0.05 to -0.08 MPa.

[0038] In some embodiments, the vacuum extraction time in step 2) is 45-60 min.

[0039] The present invention further provides use of the polymer cement waterproof coating for building waterproofing.

[0040] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0041] The polymer cement waterproof coating of the present invention can be constructed at a low temperature of minus ten degrees and cured to form a film, and the coating film performance meets the coating index required by GBT23445. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0043] Example 1

[0044] This embodiment provides a polymer cement waterproof coating, and the preparation method thereof is as follows:

[0045] Ingredients:

[0046] Precursor of liquid component A: 60wt% elastic acrylate emulsion (50% solid content, i.e. 30wt% acrylate polymer, 30wt% water), 0.2wt% organosilicon defoamer, 39.3wt% propylene glycol, 0.5wt% sodium polyacrylate (its molecular weight is about 300,000).

[0047] Powder component B: 30wt% of 42.5 ordinary silica cement, 67wt% of 200 mesh quartz sand, 2% of lithium chloride, and 1.0wt% of water reducer.

[0048] Production process:

[0049] Liquid component A: first disperse sodium polyacrylate into propylene glycol, then put other raw materials into a vacuum heating stirring kettle equipment in turn, start the stirring kettle, heat to 85 degrees, and use a vacuum pump for vacuum extraction (negative pressure is pumped to -0.05MPa). After a weight loss of 30%, liquid component A can be obtained.

[0050] In the liquid component A, by weight percentage, water is 8.0%, defoamer is 0.29%, sodium polyacrylate is 0.71%, acrylate polymer is 42.86%, and propylene glycol is 48.14%.

[0051] Liquid component B: All raw materials are put into the stirring equipment in sequence, and component B is obtained after stirring for 20 minutes;

[0052] Performance Test:

[0053] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 8.0%.

[0054] After the A and B components were mixed in a weight ratio of 1:2, a film with a thickness of 1.5 mm was coated and placed in a -10 degree (minus 10 degrees) low temperature box for curing for 10 days. The performance was tested according to GBT23445-2009 standard. The results are shown in Table 1 below.

[0055] Example 2

[0056] This embodiment provides a polymer cement waterproof coating, and the preparation method thereof is as follows:

[0057] Ingredients:

[0058] Precursor of liquid component A: 70wt% elastic acrylate emulsion (50% solid content, namely 35wt% acrylate polymer, 35wt% water), 0.5wt% organosilicon defoamer, 27.0wt% propylene glycol, 2.5wt% sodium polyacrylate.

[0059] Powder component B: 40wt% of 42.5 ordinary silica cement, 58wt% of 200 mesh quartz sand, 1% of lithium chloride, and 1.0wt% of water reducer.

[0060] Production process:

[0061] Liquid component A: first disperse sodium polyacrylate into propylene glycol, then put other raw materials into vacuum heating stirring kettle equipment in sequence, start the stirring kettle, heat to 85 degrees, and use a vacuum pump for vacuum extraction. After a weight loss of 30%, liquid component A can be obtained.

[0062] In the liquid component A, by weight percentage, water is 11.0%, defoamer is 0.71%, sodium polyacrylate is 3.57%, acrylate polymer is 50.00%, and propylene glycol is 34.72%.

[0063] Liquid component B: All raw materials are put into the stirring equipment in sequence, and component B is obtained after stirring for 20 minutes;

[0064] Performance Testing:

[0065] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 11.0%.

[0066] After the A and B components were mixed in a weight ratio of 1:1.7, a 1.5 mm thick film was coated and placed in a -10 degree (minus 10 degrees) low temperature box for curing for 10 days. The performance was tested according to GBT23445-2009 standard. The results are shown in Table 1 below.

[0067] Example 3

[0068] This embodiment provides a polymer cement waterproof coating, and the preparation method thereof is as follows:

[0069] Ingredients:

[0070] Precursor of liquid component A: 65wt% elastic acrylate emulsion (50% solid content, namely 32.5wt% acrylate polymer, 32.5wt% water), 0.2wt% organosilicon defoamer, 34.3wt% propylene glycol, 0.5wt% sodium polyacrylate.

[0071] Powder component B: 30wt% of 42.5 ordinary silica cement, 66wt% of 200 mesh quartz sand, 3% of lithium chloride, and 1.0wt% of water reducer.

[0072] Production process:

[0073] Liquid component A: first disperse sodium polyacrylate into propylene glycol, then put other raw materials into vacuum heating stirring kettle equipment in sequence, start the stirring kettle, heat to 85 degrees, and use a vacuum pump for vacuum extraction. After a weight loss of 30%, liquid component A can be obtained.

[0074] In the liquid component A, by weight percentage, water is 7.5%, defoamer is 0.28%, sodium polyacrylate is 0.71%, acrylate polymer is 46.43%, and propylene glycol is 45.08%.

[0075] Liquid component B: All raw materials are put into the stirring equipment in sequence, and component B is obtained after stirring for 20 minutes;

[0076] Performance Test:

[0077] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 7.5%.

[0078] After the A and B components were mixed in a weight ratio of 1:1.5, a film with a thickness of 1.5 mm was coated and placed in a -10 degree (minus 10 degrees) low temperature box for curing for 10 days. The performance was tested according to GBT23445-2009 standard. The results are shown in Table 1 below.

[0079] Example 4

[0080] This embodiment provides a polymer cement waterproof coating, and the preparation method thereof is as follows:

[0081] Ingredients:

[0082] Precursor of liquid component A: 60wt% elastic acrylate emulsion (50% solid content, namely 30wt% acrylate polymer, 30wt% water), 0.4wt% organosilicon defoamer, 36.6wt% propylene glycol, 3wt% sodium polyacrylate.

[0083] Powder component B: 35wt% of 42.5 ordinary silica cement, 63wt% of 200 mesh quartz sand, 1% of lithium chloride, and 1.0wt% of water reducer.

[0084] Production process:

[0085] Liquid component A: first disperse sodium polyacrylate into propylene glycol, then put other raw materials into vacuum heating stirring kettle equipment in sequence, start the stirring kettle, heat to 85 degrees, and use a vacuum pump for vacuum extraction. After a weight loss of 40%, liquid component A can be obtained.

[0086] In the liquid component A, by weight percentage, water is 10.0%, defoamer is 0.67%, sodium polyacrylate is 5.00%, acrylate polymer is 50.00%, and propylene glycol is 34.33%.

[0087] Liquid component B: All raw materials are put into the stirring equipment in sequence, and component B is obtained after stirring for 20 minutes;

[0088] Performance Test:

[0089] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 10.0%.

[0090] After the A and B components were mixed in a weight ratio of 1:1.7, a 1.5 mm thick film was coated and placed in a -10 degree (minus 10 degrees) low temperature box for curing for 10 days. The performance was tested according to GBT23445-2009 standard. The results are shown in Table 1 below.

[0091] Example 5

[0092] This embodiment provides a polymer cement waterproof coating, and the preparation method thereof is as follows:

[0093] Ingredients:

[0094] Precursor of liquid component A: 70wt% elastic acrylate emulsion (50% solid content, namely 35wt% acrylate polymer, 35wt% water), 0.2wt% organosilicon defoamer, 27.5wt% propylene glycol, 2.3wt% sodium polyacrylate.

[0095] Powder component B: 45wt% of 42.5 ordinary silica cement, 53.5wt% of 200 mesh quartz sand, 0.5% of lithium chloride, and 1.0wt% of water reducer.

[0096] Production process:

[0097] Liquid component A: first disperse sodium polyacrylate into propylene glycol, then put other raw materials into vacuum heating stirring kettle equipment in sequence, start the stirring kettle, heat to 85 degrees, and use a vacuum pump for vacuum extraction. After a weight loss of 40%, liquid component A can be obtained.

[0098] In the liquid component A, by weight percentage, water is 12.0%, defoamer is 0.33%, sodium polyacrylate is 3.83%, acrylate polymer is 58.33%, and propylene glycol is 25.51%.

[0099] Liquid component B: All raw materials are put into the stirring equipment in sequence, and component B is obtained after stirring for 20 minutes;

[0100] Performance Test:

[0101] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 12.0%.

[0102] After the A and B components were mixed in a weight ratio of 1:1.7, a 1.5 mm thick film was coated and placed in a -10 degree (minus 10 degrees) low temperature box for curing for 10 days. The performance was tested according to GBT23445-2009 standard. The results are shown in Table 1 below.

[0103] Comparative Example 1

[0104] This comparative example provides a polymer cement waterproof coating, wherein the liquid component A does not contain sodium polyacrylate:

[0105] Precursor of liquid component A: 60 wt% of elastic acrylic emulsion (50% solid content, namely 30 wt% of acrylic polymer and 30 wt% of water), 0.2 wt% of organosilicon defoamer and 39.8 wt% of propylene glycol.

[0106] Powder component B: 30wt% of 42.5 ordinary silica cement, 67wt% of 200 mesh quartz sand, 2% of lithium chloride, and 1.0wt% of water reducer.

[0107] Production process:

[0108] Liquid component A: Put all raw materials into the vacuum heating stirring kettle equipment in turn, start the stirring kettle, heat to 85 degrees, and use a vacuum pump to perform vacuum extraction. After a weight loss of 30%, liquid component A can be obtained.

[0109] The water content of the liquid component A was tested using a Calfisch moisture meter, and the result was 8.0%. However, the viscosity of the liquid component A increased significantly, and it could not be mixed with the powder component B to prepare a waterproof coating.

[0110] Comparative Example 2

[0111] This comparative example provides a polymer cement waterproof coating, and its preparation process is basically the same as that of Example 1, except that the sodium polyacrylate in the precursor of the liquid component A is replaced by a traditional sodium polyacrylate dispersant, whose number average molecular weight is less than 10,000, and the main chain of the dispersant is a polyether structure, and the side chain is a sodium acrylate structure grafted on the polyether main chain. The polymer structure is significantly different from the sodium polyacrylate in Example 1. The coating results are shown in Table 1 below.

[0112] Comparative Example 3

[0113] This comparative example provides a polymer cement waterproof coating, and its preparation process is basically the same as that of Example 1, with the only difference being that the vacuum extraction time during the preparation of liquid component A is reduced so that the water content of liquid component A is 21%. As a result, the coating freezes and cracks in a low-temperature box at minus ten degrees, and cannot form a film.

[0114] Comparative Example 4

[0115] This comparative example provides a polymer cement waterproof coating, and its preparation process is basically the same as that of Example 1, except that lithium chloride is not added to the powder component B, and the powder component B includes 32 wt% of 42.5 ordinary silica cement, 67 wt% of 200 mesh quartz sand, and 1.0 wt% of water reducer. The coating results are shown in Table 1 below.

[0116] Table 1 Performance of polymer cement waterproof coatings in various embodiments and comparative examples

[0117]

[0118] In Table 1 above, heat-treated bonding strength refers to the bonding strength after treatment at 60°C for 168 hours; -10 degree film-forming property meets the requirements of GBT23445.

[0119] It can be seen that the present invention uses polymer emulsion and propylene glycol in liquid component A at the same time, controls the lower water content and the appropriate amount of propylene glycol in liquid component A, and adds lithium chloride in component B, so that the waterproof coating can form a film in an environment of minus ten degrees, and the coating performance can be guaranteed.

[0120] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0121] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A polymer cement waterproof coating, characterized in that: The polymer cement waterproof coating comprises component A and component B; Calculated by weight percentage of component A, component A includes: 35%-60% of film-forming polymer, 5%-20% of water, 30%-50% of propylene glycol, and 0.6%-5.3% of sodium polyacrylate; calculated by weight percentage of component B, component B includes: 25%-45% of cement, 45%-75% of quartz sand, and 0.5%-3% of lithium chloride.

2. The polymer cement waterproof coating according to claim 1, characterized in that: The film-forming polymer is selected from a combination of one or more of acrylate polymers, styrene-acrylate polymers and silicone-acrylate polymers; preferably, the film-forming polymer is an acrylate polymer; and / or the mass ratio of component A to component B is 1:1.5-2.0; and / or the number average molecular weight of the sodium polyacrylate is 100,000 to 400,000.

3. The polymer cement waterproof coating according to claim 1, characterized in that: The component A further comprises an auxiliary agent, which is selected from one or more combinations of defoamers, preservatives, color pastes and wetting agents; preferably, the auxiliary agent is a defoamer; and / or, the component B further comprises an auxiliary agent, which is selected from one or more combinations of water reducers, defoamers, preservatives, color pastes and wetting agents; preferably, in terms of weight percentage of component B, component B comprises 0.2%-1.0% of the auxiliary agent.

4. The polymer cement waterproof coating according to claim 3, characterized in that: In terms of weight percentage of component A, component A includes 35%-60% of film-forming polymer, 5%-20% of water, 30%-50% of propylene glycol, and sodium polyacrylate. 0.6%-5.3%, defoaming agent 0.23%-0.9%.

5. The polymer cement waterproof coating according to claim 1, characterized in that: The component A is obtained by vacuum extraction of a precursor of the component A; In terms of weight percentage, the precursor of component A includes: 30%-40% film-forming polymer, 25%-40% water, 30%-40% propylene glycol, and 0.5%-3.0% sodium polyacrylate; preferably, the precursor of component A also includes an auxiliary agent, and the auxiliary agent is selected from a combination of one or more of a defoamer, a preservative, a color paste, and a wetting agent; more preferably, the auxiliary agent is a defoamer; particularly preferably, in terms of weight percentage, the precursor of component A includes 0.2%-0.5% of a defoamer.

6. The polymer cement waterproof coating according to claim 5, characterized in that: The component A is prepared by a preparation method comprising the following steps: dispersing the sodium polyacrylate in the propylene glycol, adding other raw materials of the precursor of the component A, heating, and vacuum extraction to obtain the component A.

7. The polymer cement waterproof coating according to claim 1, characterized in that: The cement is selected from white cement, gray cement, or a combination of the two; preferably, the cement is white cement; more preferably, the cement is 42.5 white cement.

8. The method for preparing the polymer cement waterproof coating according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: 1) dispersing sodium polyacrylate in propylene glycol, adding other raw materials of the precursor of component A, stirring and mixing, and obtaining the precursor of component A; 2) heating the precursor of the component A and vacuum extracting to obtain the component A; 3) Mixing the component A and the component B to obtain the polymer cement waterproof coating.

9. The preparation method according to claim 8, characterized in that: The stirring and mixing in step 1) is carried out in a vacuum stirring device; and / or, the heating temperature in step 2) is 80-100° C.; and / or, the vacuum extraction in step 2) is carried out at a negative pressure of -0.05 to -0.08 MPa; and / or, the vacuum extraction time in step 2) is 45-60 min.

10. Use of the polymer cement waterproof coating according to any one of claims 1 to 7 for building waterproofing.

Citation Information

Patent Citations

  • Polymer cement waterproofing coating capable of being used in low temperature environment

    CN105130321A

  • Cement waterproofing coating, and preparation method and application thereof

    CN111117314A